СALCULATION OF THE VERTICAL GATING SYSTEMS WITH USAGE OF STANDARD ELEMENTS - A. A. Tonkovich; A. A. Skvortsov (Литьë и металлургия)
Methodology of the calculation of the vertical gating systems for DISA automatic lines with use of the standardized elements is given in the article. The example of calculation of the gating system for a concrete article and results of modeling of the developed gating system with use of packages of the applied programs ProCast, Poligon are presented. The example of a choice of the standard feeder on the cooling module is given.